2020
DOI: 10.1038/s41598-020-68796-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis of primary human skeletal muscle cells during myogenic progression

Abstract: Skeletal muscle constitutes more than 30% of total body mass using substrates such as glycogen, glucose, free fatty acids, and creatinine phosphate to generate energy. consequently, multinucleated myofibers and resident mononucleated stem cells (satellite cells) generate several metabolites, which enter into circulation affecting the function of other organs, especially during exercise and atrophy. The present study was aimed at building a comprehensive profile of metabolites in primary human skeletal muscle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 36 publications
2
35
0
Order By: Relevance
“…Ashok Kumar et al Con rmed the up regulation of phenylalanine, tyrosine and tryptophan biosynthesis in the process of muscle cell differentiation, suggesting that these metabolites have important signi cance in muscle regeneration and pathology [55]. In the muscle atrophy of hind limb unloading, we found that all the substances in this metabolic network decreased signi cantly.…”
Section: Disscusionsupporting
confidence: 54%
“…Ashok Kumar et al Con rmed the up regulation of phenylalanine, tyrosine and tryptophan biosynthesis in the process of muscle cell differentiation, suggesting that these metabolites have important signi cance in muscle regeneration and pathology [55]. In the muscle atrophy of hind limb unloading, we found that all the substances in this metabolic network decreased signi cantly.…”
Section: Disscusionsupporting
confidence: 54%
“…These lowered levels may reflect a lower abundance of these amino acids in myotubes. Essential amino acids including phenylalanine and tryptophan were reported to be decreased during myotube differentiation of primary human skeletal muscle cells (Kumar et al, 2020). Similar metabolic changes are caused by induction of the FOXO1 transcription factor (Matsuda et al, 2019) that is typically induced in skeletal muscle cells (Gross et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Pantothenic acid (PA) is the primary substrate for pantothenate kinase [22] , as a rate-limiting metabolite in CoA biosynthesis. PA is the obligate precursor of acetyl-CoA, which of particular importance for cholinergic neurons [23] and participate in tricarboxylic acid cycle (TCA cycle) [24] .…”
Section: Discussionmentioning
confidence: 99%
“…PA is the obligate precursor of acetyl-CoA, which of particular importance for cholinergic neurons [23] and participate in tricarboxylic acid cycle (TCA cycle) [24] . Recent study showed that elevated concentration of CoA would lead to altered mitochondrial morphology, and lower ATP content [22] . LPS-induced BV-2 cells exhibited a decrease in the number of mitochondria and a change of mitochondrial shape.…”
Section: Discussionmentioning
confidence: 99%